Age and sex differences in in-air vocalization characteristics of spotted seal pups from newborn to 1 year old in captivity - Zhang, Peijun; Yang, Liangliang; Han, Jiabo; Yang, Yong; Lu, Zhichuang; Li, Songhai (Frontiers in Marine Science, 2022)
Acoustic parameters of spotted seals (Phoca largha), including the duration, peak frequency, and peak-to-peak source level, are reported to vary between different ages and sexes; however, to our knowledge, the vocal ontogeny of the spotted seal from newborn to 1 year old is yet to be studied. In the present study, we recorded and analyzed vocalizations of human-cared spotted seals from the Liaodong Bay colony from newborn to 1 year old, aiming to document the first-year development of seal vocalizations. We divided the spotted seal pups into four age groups (i.e., 1–3-month, 4–6-month, 7–9-month, and 10–12-month groups) for both sexes. The results show significant differences in sex patterns in sound parameters in terms of duration, peak frequency, and peak-to-peak source level. The vocalizations of female seal pups were longer in duration but lower in peak frequency and peak-to-peak source level than those of male pups. All three sound parameters were significantly different across different age groups. Specifically, the 1–3-month group had significantly lower values in duration, peak frequency, and peak-to-peak source level than the three other age groups. The 10–12-month group had significantly higher values in duration and peak-to-peak source level than the three other age groups. Our results also indicate a sex-specific development pattern of seal vocalizations from 1 year old until sexual maturity. Our findings will benefit the evaluation of anthropogenic noise impacts on spotted seal pups and further conservation of the seal population.